STRATEGI PROMOSI DALAM KONTEN MEDIA SOSIAL MIE BARACCUNG MAKASSAR - Saeni, Asrini A.; Fauzy, Ahmad (Politeknik STIA LAN Makassar, 2023)
One of the subsectors of the creative economy is the culinary sector. The growth of the culinary business has a positive effect on Indonesia's economic development because it is one of the creative economy's greatest contributors to GDP. The Indonesian economy includes MSMEs, particularly those in the food industry, which are the primary players in the sector. The COVID-19 pandemic has had a significant influence on the Indonesian economy, notably on the MSMEs in the food industry. One of the food-related MSMEs hit by the COVID-19 epidemic is Mie Baraccung Makassar. The promotion strategy used to improve the state of MSMEs is a social media advertising strategy. Due to the widespread use of social media among internet users, it is a very successful promotional tool. Mie Baraccung Makassar uses Instagram as one of their social media platforms; however, they do not yet have a plan for developing promotional content, and their Instagram feeds are not displayed in a clean and structured manner. The purpose of this study is to develop a promotion plan for Mie Baraccung Makassar's social media material in the form of promotional content employing graphic design. The objective of this study's qualitative technique, which is detailed descriptively, is to provide a thorough description of the circumstances and events. The result of this research is graphically designed promotional content for social media. This advertising content also doubles as informational material regarding Mie Baracung Makassar's goods and services.